2x-4(x+3)=x+8

Simple and best practice solution for 2x-4(x+3)=x+8 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2x-4(x+3)=x+8 equation:


Simplifying
2x + -4(x + 3) = x + 8

Reorder the terms:
2x + -4(3 + x) = x + 8
2x + (3 * -4 + x * -4) = x + 8
2x + (-12 + -4x) = x + 8

Reorder the terms:
-12 + 2x + -4x = x + 8

Combine like terms: 2x + -4x = -2x
-12 + -2x = x + 8

Reorder the terms:
-12 + -2x = 8 + x

Solving
-12 + -2x = 8 + x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-1x' to each side of the equation.
-12 + -2x + -1x = 8 + x + -1x

Combine like terms: -2x + -1x = -3x
-12 + -3x = 8 + x + -1x

Combine like terms: x + -1x = 0
-12 + -3x = 8 + 0
-12 + -3x = 8

Add '12' to each side of the equation.
-12 + 12 + -3x = 8 + 12

Combine like terms: -12 + 12 = 0
0 + -3x = 8 + 12
-3x = 8 + 12

Combine like terms: 8 + 12 = 20
-3x = 20

Divide each side by '-3'.
x = -6.666666667

Simplifying
x = -6.666666667

See similar equations:

| 37-5=4x+24 | | 7d-2=4d+13 | | x/4+3=x | | x^2+4x=4x+32 | | 5x+10=2(2x+6) | | 13-8x=143-43x | | -4(4y-8)-y=-2(y-4) | | 3y-12x=15 | | -3(y+3)=2y+21 | | h=5vt+19t^2 | | 4x^2-17x+22=4x+2 | | 3x+8=52-9x | | 8-(4-12t)+2=3t+2(7-3t) | | 3g+4(-8+3g)=1-g | | -5v-31=3(v-5) | | 6+2(3j-2)=4(l+j) | | 8=n*18 | | -8w+6(w-2)=-4 | | 3(x-6)+2x=5(x+2)-28 | | 10-10x=70-24x | | 4(x-20)=24x | | -16+x=10x | | 4(x-20)=24 | | 6p-9=-5p-42 | | 29-3x=-53 | | 30a^6-104a^5=-90a^4 | | 6p-9=5p+42 | | 5x-5y=3 | | a-2(a-16)=7a | | 5x+2=4x-5 | | 7x+18x=75 | | -5.9-3x=-2.6 |

Equations solver categories